PENGARUH PEMBERIAN BOKASHI LIMBAH DAUN KAYU PUTIH (Melaleuca cajuputi) TERHADAP PERKECAMBAHAN TREMBESI (Samanea saman) - Maria Alfira Koa; Astin Elise Mau; Norman P.L.B Riwu Kaho; Frank Samelino Tita (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Trembesi (Samanea saman) is an important greening plant that plays a significant role in climate change mitigation due to its high capacity to absorb carbon dioxide. The success of trembesi development is largely determined at the early growth stage, particularly during the germination process, which is influenced by growing media conditions and nutrient availability. The utilization of bokashi derived from cajuput leaf waste (Melaleuca cajuputi) is a potential organic fertilizer alternative that can improve the quality of growing media and support seed germination.This study aimed to determine the effect of bokashi made from cajuput leaf waste on the germination of trembesi seeds and to identify the optimum bokashi dosage. The research was conducted at the Fatukoa Permanent Nursery of BPDAS Benain Noelmina, East Nusa Tenggara Province, from July to August 2025. The experiment employed a Completely Randomized Design (CRD) with four treatments: without bokashi (P0), 200 g bokashi (P1), 300 g bokashi (P2), and 400 g bokashi (P3), each replicated three times. The observed parameters included germination percentage, germination speed index, and germination rate.The results showed that the application of bokashi from cajuput leaf waste had a highly significant effect on germination percentage and a significant effect on the germination speed index, but no significant effect on the germination rate. The best treatment was obtained at the bokashi dosage of 300 g (P2), which produced the highest germination percentage and germination speed index. Therefore, bokashi from cajuput leaf waste has strong potential to be used as an organic fertilizer to enhance the success of trembesi seed germination.Keywords: trembesi, bokashi, cajuput leaf waste, germination.